History of metallurgical development of boat propeller and keris (a comparison) / Yusniza Yem - Yem, Yusniza (2002)
This project had been proposed by Prof. Madya Dr. Mohd Nor Berhan as “History of Metallurgy in Malaysia”. This topic was proposed because of the lack information and knowledge of technical person in Malaysia in the social science area such as the history of branch of engineering. But to suit the engineering courses this project had been change its title to History of Metallurgical Development of Keris and Boat Propeller. History is a very development element in engineering and human life. People in back dated, even in the prehistory decade and civilization has growth the engineering field to fulfill their basic need and the demand at that time. They had been using man engineering technique and methodology long time ago. For example the building of 7 wonders in the world such as pyramid and Great Wall of China were using very good technique of engineering to achieve such great building. How are they manage to make such a great building in those day that being consider not modern world? Even with all advanced and updated technology that we have today, we still do not come close to the work they were doing. This project will be focusing on two different type of object which boat propeller and Keris to representing to different time, technology and process that being done on both materials. Keris had been chosen as one of the focusing object because of it always representing the old Malays culture and we still can easily find it today although it is no longer use as weapon as it uses to be. Whereas the propeller was elected was selected for this project to present today’s world because of the availability of material in our lab and we were and analysis together with and on going research.